2020
DOI: 10.1016/j.uclim.2020.100674
|View full text |Cite
|
Sign up to set email alerts
|

NO2 levels after the COVID-19 lockdown in Ecuador: A trade-off between environment and human health

Abstract: The negative effects on human health, along with the fatalities caused by the new coronavirus, have led governments worldwide to take strict measures. However, a reduction in air pollution has been found in many regions on a global scale. This study is focused on how the COVID-19 pandemic is impacting on the air quality in Ecuador, one of the most alarming cases of COVID-19 contagion in Latin America, occupying the first place as regards deaths per capita. The spatio-temporal variations in NO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 33 publications
3
33
0
3
Order By: Relevance
“…SO 2 had relatively a lower reduction, while the concentrations of O 3 increased during the lockdown period. Pacheco et al [12] reported a maximum of 23% reduction in NO 2 concentrations in Ecuador. Rodríguez-Urrego and Rodríguez-Urrego [13] in a global study of PM 2.5 in the most polluted cities, found an average reduction of 12% in PM 2.5 concentrations, while reporting the highest reductions in Bogota and Kuwait City.…”
Section: Introductionmentioning
confidence: 98%
“…SO 2 had relatively a lower reduction, while the concentrations of O 3 increased during the lockdown period. Pacheco et al [12] reported a maximum of 23% reduction in NO 2 concentrations in Ecuador. Rodríguez-Urrego and Rodríguez-Urrego [13] in a global study of PM 2.5 in the most polluted cities, found an average reduction of 12% in PM 2.5 concentrations, while reporting the highest reductions in Bogota and Kuwait City.…”
Section: Introductionmentioning
confidence: 98%
“…They also found that the global response to COVID-19 led to a sudden reduction in both greenhouse gas emissions and air pollutants. Pacheco et al (2020) reported that air quality in Ecuador was greatly improved during lockdown with a 23% decrement in the NO 2 concentration. This trend of increasing air quality was also found in Lima, Peru (Velásquez and Lara, 2020), Rio de Janeiro, Brazil ( Nakada and Urban, 2020 ) Almaty, Kazakhstan ( Kerimray et al, 2020 ), and in four Southern European cities (Nice, Rome, Valencia, and Turin; Sicard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the pandemic has resulted in a drastic reduction in global economic activities due to the health policies, physical distancing measures and mobility restrictions implemented worldwide. Quarantines have been applied in countries in all continents as a strategy to minimize the virus transmission rates, and an improvement in local air quality has been reported as a side effect in China (Pei et al, 2020;Zhang et al, 2020), India (Sharma et al, 2020;Shehzad et al, 2020), Europe (Menut et al, 2020), the United States (Chen et al, 2020a), Brazil (Dantas et al, 2020;Nakada and Urban, 2020), Ecuador (Cazorla et al, 2020;Pacheco et al, 2020), and many others, with significant reductions in the concentrations of PM2.5 and PM10, carbon monoxide (CO) and NO2. These improvements implied a short-term…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%